The Effectiveness of the 2022 Student Exercise Program in Improving the Physical Fitness of PGMI Students - Akbar, Andi Khemal; Mulyaningsih, Eka (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study examined the effectiveness of the 2022 Student Exercise Program in improving the physical fitness of PGMI students at IAIN Bone. Employing a quantitative pre-experimental design with a one-group pretest-posttest model, a sample of 20 female students was selected from a population of 240 using random sampling. Participants underwent six sessions of rhythmic aerobic exercise. Physical fitness was assessed using a standardized test for ages 16–19, including a 60-meter sprint, pull-ups, sit-ups, vertical jump, and a 1,000-meter run. Data were analyzed using descriptive and inferential statistics. A paired sample t-test revealed a significant improvement in posttest scores (t = -9.647; p = 0.000), indicating that the program effectively enhanced students’ physical fitness. These findings support the integration of structured physical activity into higher education, particularly in teacher training programs.